Learning process optimization by mathematical simulation means - Vereitina, I. (Journal of Information Technologies in Education (ITE), 2009)
The results of the study are directed to the methodic of learning process analyzes verifying and complex measures for its improving, i.e. optimal criterion definition – knowledge volume and influencing optimization parameters – activity aspects under conditions of high – grade training providing. According to the learning process optimization task mathematical simulation results on the example of foreign language it was shown that between the knowledge volume and training aspects the considerable non-linear connection exists which should be taken into consideration when making the syllabus and skills evaluation.